Tonthun : sawatdikān chumchon khon Thā Ngām Tō̜. Thā Ngām, ʻŌ̜. ʻIn Burī, Čhō̜. Sing Burī - ʻInthirā Witthayasombūn (Sathāban Phatthanā ʻOngkō̜n Chumchon, 2010)
Cost accounting for the welfare of the community organization in Tambon Tha Ngam, Sing Buri Province, Central Thailand.